Proceedings of the 3rd South-East European Conference on Computational Mechanics (SEECCM III) 2014
DOI: 10.7712/130113.4393.s2121
|View full text |Cite
|
Sign up to set email alerts
|

Resistance of Door Openings in Towers for Wind Turbines

Abstract: Abstract. In this paper, a study of resistance of a lower part of a wind tower including a door opening is presented. Nonlinear 3-D shell element models with real geometry of lower tower segment have been used to simulate the thin walled shell structure in order to study the influence of door opening on the strength of the tower. Two possible alternatives for strengthening the door openings were considered: (i) increasing thicknesses of plate around the opening and (ii) stiffening the opening by a stiffener. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…The effect of stiffened cutouts on the buckling response of cylindrical steel shells with geometric characteristics, which are typical of modern wind turbine towers, has been studied by a group of the primary author experimentally and numerically [38,39], focusing on the comparison between alternative stiffener configurations. The issue has also been addressed in the last decade by other investigators [40,41].…”
Section: Introductionmentioning
confidence: 99%
“…The effect of stiffened cutouts on the buckling response of cylindrical steel shells with geometric characteristics, which are typical of modern wind turbine towers, has been studied by a group of the primary author experimentally and numerically [38,39], focusing on the comparison between alternative stiffener configurations. The issue has also been addressed in the last decade by other investigators [40,41].…”
Section: Introductionmentioning
confidence: 99%
“…Required structural design verifications are described in pertinent recommendations [24][25][26][27] and guidelines [28][29][30]. Issues that have attracted particular attention include the arrangement of stiffening rings to improve buckling resistance [31][32][33], measures to recover the lost strength and stiffness due to the man-door opening near the tower base [34][35][36][37][38] and the design of ring flange connections between consecutive segments [39,40]. Extensive research efforts have been directed towards structural analysis and design methods [41][42][43][44][45][46][47], as well as towards optimizing the design to achieve reduced tower weight and cost [10,[48][49][50][51].…”
Section: Introductionmentioning
confidence: 99%
“…Van der Woude et al [10] performed parametric studies on base isolation systems to improve the structural response of wind turbine structures during strong earthquake events; it was concluded that the use of base isolation systems reduces possible excessive dynamic displacements of the structures in seismic zones. Tran et al [11] described the influence of the door opening on the strength of wind turbine towers by means of detailed finite element models. Do et al [12] studied the structural response of towers by taking into account fatigue due to wind loads, aiming to minimize the cost of structural steel, and to optimize the design parameters of the tower base and to achieve a longer fatigue life of the towers.…”
Section: Introductionmentioning
confidence: 99%